Primary Cutaneous Cryptococcosis: An Unusual Injection Site Infection - Guy Shalom; Amir Horev (Karger Publishers, 2020)
Primary cutaneous cryptococcosis (PCC) is an uncommonly reported entity. We describe an unusual case of PCC in an injection site of an immunocompromised patient. The specific case demonstrates a challenging treating dilemma with different alternative treatment choices. In the presented clinical setting, each choice concealed its risks and benefits. We highlight the importance of patient education for taking the appropriate measures for the disinfection of subcutaneous injection sites.